Same stock, different management: quantifying the sustainability of three shrimp fisheries in the Skagerrak from a product perspective. (23rd March 2016) - Ziegler, Friederike; Hornborg, Sara; Valentinsson, Daniel; Skontorp Hognes, Erik; Søvik, Guldborg; Ritzau Eigaard, Ole
Abstract: The northern shrimp ( Pandalus borealis L.) stock in the Skagerrak is shared by Sweden, Norway, and Denmark. Although the fishery is regulated by an annual agreement between the EU and Norway, there are also national regulations as well as differences in fleet composition and shrimp markets. In early 2014, the World Wildlife Fund gave all Skagerrak shrimp a red light in their seafood consumer guide, which led to an extensive debate, especially in Sweden, about the sustainability of this fishery. The aim of this study was to quantify a set of indicators that together give a broad picture of the sustainability of the three fisheries to provide an objective basis for a discussion on needed measures. The different indicators concerned environmental, economic or social aspects of sustainability and were quantified per tonne of shrimp landed by each country in 2012. The Danish fishery was most efficient in terms of environmental and economic indicators, while the Swedish fishery provided most employment per tonne of shrimp landed. Fuel use in all fisheries was high, also when compared with other shrimp fisheries. Interesting patterns emerged, with smaller vessels being more fuel efficient than larger ones in Sweden and Norway, with the opposite trend in Denmark. The study also demonstrated major data gaps and differences between the countries in how data are collected and made available. Various improvement options in the areas data collection and publication, allocation of quotas and enforcement of regulations resulted. Product-oriented studies could be useful to follow-up performance of fisheries over time and to identify how to best utilize the Skagerrak shrimp stock. This could involve evaluating novel solutions in terms of technology and management, based on current and future scenarios aiming to maximize societal benefits generated from this limited resource, at minimized environmental impacts.